An integrated framework for structural geology : kinematics, dynamics, and rheology of deformed rocks /: kinematics, dynamics, and rheology of deformed rocks. (2022) - Wojtal, Steven F; Blenkinsop, Tom G; Tikoff, Basil
No abstract available